Analisis Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Dalam Membayar Pajak Kendaraan Bermotor Di Samsat Kota Batam - Mortigor Afrizal Purba (LPPM Universitas Putera Batam, 2023)
This study aims to prove the existence of partial and simultaneous influence of a variable Taxpayer Awareness and Science in Taxation to the taxpayer of the Variable Compliance Paying Motor Vehicle Tax in SAMSAT Batam. The analysis used in this research is Multiple Linear Regression Analysis which has the aim to determine the regression coefficients besarknya which will show the level of influence of independent variables on the dependent variable. The results of t-test showed that the variables Consciousness Taxpayer significantly affects the Taxpayer Compliance In Paying Motor Vehicle Tax with t Count equal to 2.851 with a significance level of 0.000 and Science in Taxation to variable Taxpayer Compliance In Paying Vehicle Tax motor with t Count equal to 3.358 with a significance level of 0.000. Test results show that the F Taxpayer Awareness and Science in Taxation simultaneously influence the Taxpayer Compliance In Paying Motor Vehicle Tax with F Calculate 154.945.